IMPLEMENTATION OF AQIDAH AHKLAK LEARNING IN SHAPING THE CHARACTER OF STUDENTS IN MADRASAH - Mubarak, A. Faizul; Siti Aisa (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study describes the application of aqidah and akhlak learning in shaping students' characters in the MTs Azzainiyah II Paiton Probolinggo environment. The importance of akhlak education is very crucial in dealing with various problems of moral decline that occur among Indonesian students. Therefore, the role of schools is required to make maximum efforts in creating and improving the quality of education, both in general and religiously. The function of national education itself is to develop students' abilities and shape the character and civilization of a dignified nation, in order to educate the nation's life and create a society that has a noble attitude, is knowledgeable, creative, independent, and has broad insight. This study uses a qualitative approach with data collection techniques through observation triangulation, interviews, and documentation studies. The results of the study indicate that the planning process for the implementation of aqidah and akhlak values ​​in shaping students' characters has a very good basis and purpose. It is hoped that by implementing the values ​​of aqidah and akhlak, students can understand and practice them gradually. so that they can become better individuals. The development of aqidah and akhlak education among students aims to foster a new character that is full of responsibility. In addition, the implementation of character education integration through the subjects of faith and morals has been carried out in accordance with the applicable curriculum, referring to the learning process plan implemented in schools.